2016
DOI: 10.1007/s10689-016-9932-2
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-sparing total duodenectomy for Spigelman stage IV duodenal polyposis associated with familial adenomatous polyposis: experience of 10 cases at a single institution

Abstract: Duodenal cancer is a leading cause of death in patients with familial adenomatous polyposis (FAP). In patients with Spigelman's classification (SC) stage IV duodenal polyposis (DP), careful endoscopic surveillance by specialists or surgical intervention is mandatory. We herein report the surgical and pathological outcomes of FAP patients with SC stage duodenal polyposis undergoing pancreas-sparing total duodenectomy (PSTD), which has been rarely reported but seems optimal in such patients. PSTD and distal gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…In Japan, there is one single-center retrospective study regarding PSD (PSTD) performed in 10 patients with duodenal adenomas diagnosed with stage IV Spigelman classification. In terms of postoperative complications, four patients had pancreatic fistulas that have been managed through conservative treatment, and one patient had surgical site infection and cholangitis with low severity grade, suggesting that PSD (PSTD) is a feasible procedure [ 140 ].…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, there is one single-center retrospective study regarding PSD (PSTD) performed in 10 patients with duodenal adenomas diagnosed with stage IV Spigelman classification. In terms of postoperative complications, four patients had pancreatic fistulas that have been managed through conservative treatment, and one patient had surgical site infection and cholangitis with low severity grade, suggesting that PSD (PSTD) is a feasible procedure [ 140 ].…”
Section: Commentsmentioning
confidence: 99%
“…In a summary of the studies on PSD between 1995 and 2012, 20% of all 96 patients underwent total duodenectomy, and 80% preserved their pyloric rings [ 140 ]. Whether or not total duodenectomy is necessary remains controversial, since there is no definite conclusion regarding the risk of carcinogenesis from the remnant duodenal mucosa after PSD with preservation of the pyloric ring.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Other studies have reported even higher short-term morbidity rates (60%-76%). 50,51 Long-term morbidity (>30 days post-surgery) is also frequent, with pancreatitis (16%-21%) and exocrine pancreatic insufficiency (30%-60%) being the most common after PPD and PD, respectively. 49,52,53 The 30-day mortality rates vary from 2% to 29%.…”
Section: How Should We Intervene?mentioning
confidence: 99%
“…Endoskopické výkony by měly být prováděny preferenčně v celkové anestezii, endosko pisty zkušenými v technice a s maximálním důrazem na prevenci komplikací (léčba inhibitory protonové pumpy a zajištění pankreatického vývodu po papilek tomii stentem). Chirurgickými alternativami jsou polyp ektomie z duodenotomie a cefalická duodenopan kreatektomie, vysoce specializovaná centra provádějí i pankreas šetřící totální duodenektomii [22].…”
Section: Terapie Extrakolických Projevůunclassified